Complete genome sequences of 10 Xanthomonas oryzae pv. oryzae bacteriophages - Kovács, Tamás; Molnár, János; Varga, Ildikó; Nagy, Ildikó K.; Valappil, Sarshad Koderi; Papp, Szilvia; Vera Cruz, Casiana M.; Oliva, Ricardo; Vizi, Tímea; Schneider, György; Rákhely, Gábor (American Society for Microbiology, 2019)
Xanthomonas oryzaepv. oryzae is the causative agent of bacterial leaf blight of rice. The application of bacteriophages may provide an effective tool against this bacterium. Here, we report the complete genome sequences of 10 newly isolated OP2-likeX. oryzaepv. oryzae bacteriophages.